Selection and Characterisation of Oenococcus oeni and Lactobacillus plantarum South African Wine Isolates for Use as Malolactic Fermentation Starter Cultures - Lerm, E.; Engelbrecht, L.; du Toit, M. (South African Journal of Enology and Viticulture, 2011)
This study focused on characterising 23 Oenococcus oeni and 19 Lactobacillus plantarum strains isolated from the South African wine environment for the development of potential commercial malolactic fermentation (MLF) starter cultures. These strains were characterised with regards to oenological important characteristics, including the genetic screening for enzyme-encoding genes (enzymes that are involved/implicated in wine aroma modification, as well as enzymes pertaining to the wholesomeness of the final wine product), their fermentation capabilities, the ability to maintain viability during MLF, as well as the volatile acidity production. A total of three O. oeni and three L. plantarum strains were selected at the completion of this study. These six strains showed the most potential during the characterisation stages of the study and were able to successfully complete MLF in Pinotage wine. It was also found that L. plantarum strains displayed a more diverse enzyme profile than O. oeni strains, particularly with regards to the presence of the aroma-modifying enzymes β-glucosidase and phenolic acid decarboxylase (PAD), which implies the future use of this species in the modification of the wine aroma profile and use as commercial starter culture.